ROLE OF SERUM ALBUMIN AND COPEPTIN IN SEVERITY OF COMMUNITY-ACQUIRED PNEUMONIA - Dr. Lava; Dr. C. Prashanth; Dr. Vaibhav C Padashetty; Dr. U Sohan Kukkillaya; Dr. Kirankumara; Dr. Anusree C (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Community-acquired pneumonia (CAP) is a significant cause of morbidity and mortality worldwide. Early risk stratification is crucial for effective management. Traditional clinical scoring systems may be enhanced by objective biomarkers such as serum copeptin, a marker of physiological stress, and serum albumin, a negative acute-phase reactant. Aim: To evaluate the role of serum copeptin and albumin as markers of disease severity and predictors of outcome in patients with CAP. Methods: This observational study was conducted over six months at Mysore Medical College and Research Institute, including 100 adult patients diagnosed with CAP. Patients were classified based on Pneumonia Severity Index (PSI) scores into three groups (Class 3, 4, and 5). Serum copeptin and albumin levels were measured on admission and compared across severity groups and clinical outcomes. ROC curve analysis was performed to determine the diagnostic accuracy of both markers. Results: Mean serum copeptin levels increased significantly with PSI class (PSI 3: 11.63 ng/mL; PSI 5: 30.23 ng/mL). Non-survivors had a mean copeptin level of 32.37 ng/mL compared to 18.46 ng/mL in survivors. A cutoff of 23.7 ng/mL predicted severe CAP with 90.63% sensitivity and 92.65% specificity. Serum albumin levels decreased with increasing severity (PSI 3: 3.45 g/dL; PSI 5: 3.03 g/dL). Non-survivors had lower albumin (2.56 g/dL) compared to survivors (3.39 g/dL), with a mortality prediction cutoff of 2.87 g/dL (sensitivity 88.2%, specificity 94%). Conclusion: Serum copeptin is a highly sensitive and specific biomarker for predicting severity and mortality in CAP. Serum albumin, while less specific, provides supportive prognostic information. Both markers are independent of age and sex and can enhance clinical decision-making when used alongside established severity scores.